Facets of Corporate Social Responsibility in Today’s Era - A Case Study Mahindra and Mahindra Ltd - Kaur, Harsh Vineet; Kaur, Gurvinder (Prabandhan: Indian Journal of Management, 2010)
A business doesn’t exist in isolation, simply as a way of making money. Customers, suppliers and the local community are all affected by a business. Products, and the way you make them, have an impact on the environment. Corporate Social Responsibility (CSR) takes all this into account and helps the business to create and maintain effective relationships with your stakeholders. It isn’t about being ’right on’, or mounting an expensive publicity exercise. It means taking a responsible attitude, going beyond the minimum legal requirements and following straightforward principles that apply, whatever the size of your business. Corporate Social Responsibility is a function of operating a business that meets or exceeds the ethical, legal, commercial and public expectations that society has of business. Corporate Social Responsibility is one such niche area of Corporate Behavior and Governance that needs to get aggressively addressed and implemented tactfully in the organizations. ’Benefit From Corporate Social Responsibility’ -publicity like this can be a key part of using CSR to win contracts. People want to buy from businesses they respect. CSR can be particularly effective for targeting ethical companies, the public sector and not-for-profit organizations. At the same time, you should see CSR as part of a continuing process of building long-term value. Everything you do should help to improve your reputation and encourage customers and other stakeholders to want to be involved with you. A business that buys recycled paper - but exploits its customers and ignores the community - has missed the point. Effective CSR like this helps you continue to differentiate yourself. Even with dozens of competitors, a real commitment to CSR lets you stand out.